Eispa enterprise the magic goggles - Meli, Siti Zulaikha; Jamaluddin, Syarfa Afifah; Ismail, Sofea Alini; Che Zawawi, Nurhazleen Izyan; Abdul Rahman, Auni Fathini (2021)
Nowadays, many people prefer and tend to start a business including us. First of all, I will explain first about our business. EISPA is the name that has been chosen to be our business name. The name EISPA is a combination of the first letters of all the names of our group members. The nature of our company is manufacturing business. This is because, we make products from raw materials before being produced for sale to customers. We have agreed to start a business on 1st January, 2020. Because in our opinion, it is good to start thenew year with something fresh. The product we produce is named "Magic Goggle". We estimate that the mode of use required to start this business is RM 350,000. Every entrepreneur definitely wants his business to succeed. We want our product to be known to all because of its own characteristics that can give advantages to consumers and also have a bright future. In addition, we also hope that this business can stand stable in the market. We adhere to our vision and mission to be the most desirable equipment for snorkeling by 2031 and to fight the fear of not seeing anything in the ocean. Next, we have also designed a special logo to show our professional side. Every line in the logo has an implicit meaning. Our organization's motto is do the best, ignore the rest. In addition, we also hope to provide good service and high quality magic glasses so that everyone can enjoy better snorkeling. Every business should start with careful planning. This is because before starting a business, the kite must first evaluate the viability and growth potential of the project to see how far the business to be run can be accepted and accepted in the market. In addition, to apply for a loan or financing facility from the relevant financial institution. This is because, we need sufficient funds to start a business. The funds needed are not in small amounts but the cost required is enormous. Therefore, we only need a loan from a true and trustworthy bank or institution. This is because we want to avoid problems in the future. With business proposals, it is very possible that our loan application will be easier and faster. Further, act as a guide for the proposed business management. With this, the business can be run and run more systematically without problems because it has guidelines and references. Furthermore, with this we can also produce good and high quality products. Finally, to allocate business resources affectively. This is also a short-term strategy or plan devised to achieve future targets about this business. This is because we must have a target to be achieved so that we can devise a strategy to achieve that target. Every business has its own organizational chart as well as our business. This business is led and run by a woman named Auni Fathini. She is a woman who has held the position of general manager. For everyone's information, the general manager is responsible for all departmental operations or company operations. These include in generating income, managing and maintaining the goodness of staff, controlling costs and more. In addition.